Penerapan Senayan Library Managements System (SLiMS) dalam Manajemen Layanan Perpustakaan Ngudi Ilmu Desa Ngemplak - Firda Nugraheni Cahyaningtyas; Mega Arif Marintan (Jurnal Gema Pustakawan, 2024)
Libraries, as information institutions, are required to adapt to the latest technological developments continuously. One of the efforts made by libraries is to implement automation systems to manage library services effectively. With an automation system, various library services can be completed in a very short time, even in minutes or seconds. A popular automation system used by libraries is the Senayan Library Management System (SLiMS). Ngudi Ilmu Library has adopted SLiMS to manage its services. This research aims to determine how practical the application of library automation systems is in library service management at Ngudi Ilmu Library in Ngemplak. The research method used is qualitative research with data analysis from interviews with librarians from Ngudi Ilmu Library in Ngemplak as sources. The results of the study show that the implementation of SLiMS at Ngudi Ilmu Library has a significant impact. The implementation of SLiMS greatly assists librarians in managing various library services, especially circulation services. With the automation system, the circulation process can be carried out quickly and efficiently.  Keywords: automation system, services, library